CAN RADIOLOGICAL ASSESSMENT OF THE DEGREE OF CAROTID ARTERY STENOSIS BE USED AS AN INDEPENDENT PREDICTOR FOR THE RISK OF RECURRENT ISCHEMIC STROKE IN PATIENTS WITH PRIOR ISCHEMIC STROKE? A SYSTEMATIC REVIEW - Haekal Mahargias; Febrina Mayasari Gunawan; Mutiara Amalia (International Medical Journal Corp. Ltd, 2025)
Introduction: Recurrent ischemic stroke poses a significant clinical challenge, with carotid artery stenosis traditionally considered a major risk factor. However, whether the degree of stenosis alone independently predicts recurrence remains debated. This systematic review evaluates whether radiological assessment of carotid stenosis degree can serve as an independent predictor for recurrent ischemic stroke in patients with prior stroke. Methods: A systematic review was conducted following standardized screening criteria. Studies were included if they enrolled patients with confirmed prior ischemic stroke, assessed carotid stenosis using radiological methods (CT angiography, MR angiography, duplex ultrasound, or conventional angiography), quantified stenosis degree, and reported recurrent stroke outcomes. Data extraction encompassed study populations, stenosis assessment methods, recurrent stroke outcomes, multivariable analyses, and alternative predictors. Results: Fifty-nine studies were included, comprising 15 randomized controlled trials, 18 systematic reviews, and 26 cohort studies. The association between stenosis degree and recurrent stroke was heterogeneous. Large trials demonstrated significant independent prediction (POINT trial: OR 2.77, 95% CI 1.78-4.31; ENOS trial: OR 1.88, 95% CI 1.44-2.44 for ≥70% stenosis). However, other studies found no significant association (Mingyong Liu et al., 2014: annual risk 3.3% vs 4.7%, P=0.691; NAVIGATE-ESUS: HR 1.11, 95% CI 0.73-1.69). Plaque characteristics, particularly intraplaque hemorrhage, demonstrated stronger predictive value (HR 4.59-11.7) than stenosis degree alone. Cerebrovascular reserve also outperformed stenosis measurement (P=0.003 vs P=0.691). Recurrent events concentrated within the first 7-14 days post-index stroke (58% within 14 days), emphasizing the need for rapid risk stratification. Discussion: The predictive value of stenosis degree varies by clinical context, being most reliable in recently symptomatic severe (≥70%) stenosis but diminishing in moderate stenosis or when plaque vulnerability markers are considered. The pathophysiological basis for these findings relates to stenosis reflecting luminal narrowing without capturing plaque instability or hemodynamic compromise. Conclusion: Radiological assessment of carotid stenosis degree can serve as an independent predictor of recurrent ischemic stroke, but with moderate predictive accuracy (approximately 70%). Its clinical utility is enhanced when combined with plaque vulnerability markers, hemodynamic assessment, and consideration of timing from index event. Future risk stratification should integrate these multidimensional factors.